Production and partial characterization of keratinase produced by a microorganism isolated from poultry processing plant wastewater - Tapia, Daniel M. T. [UNESP]; Contiero, Jonas [UNESP] (My University, 2008)
A Streptomyces was isolated from poultry plant wastewater, showed high keratinolytic activity when cultured on feather meal medium. Optimum keratinolytic activity was observed at 40°C and pH 8.0. The enzyme also showed to be stable between 40 and 60°C. The keratinolytic activity was not inhibited by EDTA, DMSO and Tween 80. On the other hand, CaCl2, ZnCl2, and BaCl2 slightly inhibited the keratinolytic activity. The Streptomyces isolated might be useful in leather, keratin waste treatment, animal feeding industry, and also cosmetic industry. © 2008 Academic Journals.
Keywords: Keratinase; Streptomyces; Wastewater; barium chloride; calcium chloride; catalase; dimethyl sulfoxide; edetic acid; keratinase; lysine decarboxylase; ornithine decarboxylase; oxidoreductase; polysorbate 80; triacylglycerol lipase; zinc chloride; animal food; cosmetic industry; enzyme activity; enzyme analysis; enzyme assay; enzyme inhibition; enzyme synthesis; fungus growth; fungus isolation; Gram staining; pH measurement; poultry; temperature measurement; waste water; waste water management; Animalia